Introduction to Probability and Statistics for Engineers and Scientists - Ross, Sheldon M. (University of Southern California, Los Angeles, USA, 2015)
This book has been written for an introductory course in statisticsor inprobability and statistics for students in engineering, computer science, mathematics, statistics, and the natural sciences. As such it assumes knowledge of elementary calculus...